1989
DOI: 10.1099/0022-1317-70-3-639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for At Least Four Antigenic Sites on Type O Foot-and-Mouth Disease Virus Involved in Neutralization; Identification by Single and Multiple Site Monoclonal Antibody-resistant Mutants

Abstract: SUMMARYNeutralizing monoclonal antibodies raised against type 0 foot-and-mouth disease virus have been characterized on the basis of their reactivity with a panel of single site monoclonal antibody-resistant mutants which had defined three antigenic sites. Five antibodies neutralized all these mutants, but by selecting further single site mutants with one of these antibodies it was possible to define a fourth site involved in virus neutralization. Two monoclonal antibodies still neutralized these mutants and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 13 publications
3
66
0
Order By: Relevance
“…Attachment of other viruses may be reduced by the binding of antibody but the magnitude of the reduction in attachment makes only a contribution to the neutralization found. A very clear illustration of the fact that IgG does not necessarily affect attachment is provided by those neutralization escape mutants which still bind their selecting monoclonal antibody [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…Attachment of other viruses may be reduced by the binding of antibody but the magnitude of the reduction in attachment makes only a contribution to the neutralization found. A very clear illustration of the fact that IgG does not necessarily affect attachment is provided by those neutralization escape mutants which still bind their selecting monoclonal antibody [35,41].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these mAbs were against Euro-Asian serotypes A, O and C (Xie et al, 1987;Thomas et al, 1988;Baxt et al, 1989;Bolwell et al, 1989;McCahon et al, 1989;Kitson et al, 1990;Saiz et al, 1991;Crowther et al, 1993a). Only one report described the mapping of epitopes to a SAT2 virus (RHO/1/48) isolated in 1948 (Crowther et al, 1993b), with residues 147-149 and 156 in the flexible and surface-exposed G-H loop of 1D proven to be important in in vitro neutralization by a mAb.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophilicity and deduced surface exposure were also considered for each residue and highly variable regions correlated with regions of significant hydrophilicity (see Supplementary material). Comparison of the P1 amino acid sequences of SAT1 and 2 with type A and O sequences, revealed that many of the SAT1 and 2 hypervariable regions corresponded or were located in close proximity to previously identified immuno-dominant sites on types O and A (Table 4; Xie et al, 1987;Thomas et al, 1988;Baxt et al, 1989;Bolwell et al, 1989;McCahon et al, 1989;Kitson et al, 1990;Saiz et al, 1991;Crowther et al, 1993a). Some hypervariable regions were located within flexible structural loops or downstream of protease cleavage sites.…”
Section: Comparison Of Amino Acid Variation Within the Sat1 And 2 Sermentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of two viruses closely related to G67 are known, namely virus OIBFS (Acharya et al, 1989), which differs from G67 by 11 mutations in the four capsid proteins, and virus O~K (manuscript in preparation) which differs at only six positions. G67 is, in fact, derived from virus O~K by growing O~K in vitro in the presence of the selective pressures imposed by antibodies recognising the virus (Kitson, McCahon & Belsham, 1990;McCahon et al, 1989).…”
Section: Introductionmentioning
confidence: 99%